Participatory Processing Data on Matooke generated by NARL & Bioversity in Uganda - Marimo, Pricilla; Akankwasa, Kenneth; Nowakunda, Kephas; Asasira, Moreen (2023)
This dataset contains data generated during the Activity 4 or Step 3 - Participatory Processing Diagnosis and Quality Characteristics performed by the NARL & Bioversity team in Uganda on Matooke within the RTBfoods project (following the Methodological Guidance).